Impact of Television on Rural Development - Nazari, Mohammad Reza (2010)

(untitled)
Television has proved to be a profound means of communication and potentially capable of leaving tremendous effect on the society. Undoubtedly, television is an influential and appealing medium, capable to draw the attention of too many viewers regardless of the literacy or illiteracy of its audiences. Although the cost and expenditure of television exceeds than that of radio, it is more effective and powerful from the educational viewpoint. The purpose of this study was to evaluate the role of television as an educational tool to enhancement of farmers’ knowledge. This study was a randomized subject, pretest-posttest design among farmers who were working and residing in the province Kohgiluyeh va Buyer Ahmad, Iran. The subjects of the study including 161 farmers were selected randomly from rural area in Kohgiluyeh va Buyer Ahmad province. After determining educational goals of the study, a questionnaire was prepared as pre and post test. Based on educational contents, one TV program were produced which turn round fighting against agricultural pests, and correct method of using agricultural poisons. Participants responded to pre test one week before broadcasting television program through provincial Broadcast center of Kohgiluyeh va Buyer Ahmad. The post test was conducted after broadcasting TV program. Almost of the farmers in this study were male (90.1%) and married (80%).Mean age of the farmers was 41.65 ±14.69 years. Among the respondents 37 people were illiterate (23%). The finding of the study showed that educational intervention through TV program resulted a significant knowledge enhancement from 3.73 to 6.26 out of 10 which was proven the effective role of television to improve awareness of farmers ( p<0.001). Media remains a vital part of development and farming systems and intervention of education in agriculture will be more fruitful if it is conveyed through television and will result in heightening the farmers’ awareness.